2017
DOI: 10.1523/jneurosci.0628-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Local Inhibition of PERK Enhances Memory and Reverses Age-Related Deterioration of Cognitive and Neuronal Properties

Abstract: Protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK) is one of four known kinases that respond to cellular stress by deactivating the eukaryotic initiation factor 2 α (eIF2α) or other signal transduction cascades. Recently, both eIF2α and its kinases were found to play a role in normal and pathological brain function. Here, we show that reduction of either the amount or the activity of PERK, specifically in the CA1 region of the hippocampus in young adult male mice, enhances neuronal excitability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 71 publications
2
85
0
Order By: Relevance
“…PERK is a key regulator of eIF2-dependent translation, which is a key molecular process underlying learning and memory formation 2426 . To determine whether the conditional deletion of PERK in DA neurons impacts cognitive, as well as motor function, we examined 3- and 12-month old PERK f/f DAT-Cre mice and age-matched littermate WT DAT-Cre mice in a series of behavioral tasks to test learning and memory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PERK is a key regulator of eIF2-dependent translation, which is a key molecular process underlying learning and memory formation 2426 . To determine whether the conditional deletion of PERK in DA neurons impacts cognitive, as well as motor function, we examined 3- and 12-month old PERK f/f DAT-Cre mice and age-matched littermate WT DAT-Cre mice in a series of behavioral tasks to test learning and memory.…”
Section: Resultsmentioning
confidence: 99%
“…Classically, eIF2α-mediated translational control in the brain has been studied in the context of synaptic plasticity as well as learning and memory processes 5,56 , with most of the studies focusing on molecular manipulation in excitatory neurons 17, 25, 26 . Our findings reveal a previously unrecognized role of PERK-eIF2α-mediated translation in DA neurons and provide molecular insights into the pathophysiology of motor and cognitive impairments when this type of translational control is disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…Although rarely discussed in the past literature, EXOSC4 is known to be related to the protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK, encoded by the EIF2AK3 gene), which regulates gene expression [38]. A recent study reported that locally reduced PERK expression or activity could enhance neuronal excitability and improve memory and cognitive function in young mice [39]. Another study provided evidence that PERK is a key regulator of memory impairments and neurodegeneration in Alzheimer's disease [40].…”
Section: Discussionmentioning
confidence: 99%
“…Protein translation overload is temporarily halted by PERK; hence, the function of PERK is extremely important for easing the UPR. PERK is functionally essential for deciding neuronal fate because it is a crucial mediator of ER stress [115], and numerous pharmacological agents are capable of targeting the UPR and ER stress components. Thus, existing approaches to treat ICH can be combined with pharmacological agents that can directly activate or deactivate ER stress components, which might play a critical role in alleviating post-ICH symptoms.…”
Section: Er Stress Components and Ich Therapeutic Strategiesmentioning
confidence: 99%